(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Carbon nanotubes (CNTs) were grown over 12Mo:18Co:70MgO catalyst at 500, 700 and 900° C from C2H2 decomposition for 30 minutes using chemical vapor deposition (CVD) method. The highest yield of CNTs was observed at 700O C. The lowest diameter of CNTs appeared at 900° C. Quadruple mass spectroscopy (QMS) study on the species generated from the catalytic decomposition of C2H2 identified that the catalyst consumed C species during the growth stage of CNTs. The consumption period of C varied with temperature and showed a close relationship with the carbon yield. At 500, 700 and 900°C, the consumption periods were 12, 35 and 20 min, respectively, and the corresponding carbon yields were 7, 385 and 89%. From the XRD analysis of catalyst surface, and XRD and Raman analysis of the CNTs, it was realized that Co particles released from Co3O4, CoMoO4 and CoO-MgO were participated in CNTs growth at 500, 700 and 900° C, respectively. The Co particles acted as the transporting medium of carbon to grow CNTs. The tubes are MWNTs and grown by tip growth mode. Bangladesh J. Sci. Ind. Res. 42(2), 105-114, 2007